2017
DOI: 10.1073/pnas.1707323114
|View full text |Cite
|
Sign up to set email alerts
|

Reviewer bias in single- versus double-blind peer review

Abstract: SignificanceScientific peer review has been a cornerstone of the scientific method since the 1600s. Debate continues regarding the merits of single-blind review, in which anonymous reviewers know the authors of a paper and their affiliations, compared with double-blind review, in which this information is hidden. We present an experimental study of this question. In computer science, research often appears first or exclusively in peer-reviewed conferences rather than journals. Our study considers full-length s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
395
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(406 citation statements)
references
References 21 publications
7
395
1
3
Order By: Relevance
“…Our finding that the gender of the last authors was associated with a significant difference in 614 the rate at which full submissions were accepted at eLife stands in contrast with a number of 615 previous studies of journal peer review that reported no significant difference in outcomes of 616 papers submitted by male and female authors [85][86][87], or differences in reviewer's evaluations 617 based on the author's apparent gender [88]. This discrepancy may be explained in part by 618 eLife's unique context, policies, or the relative selectivity of eLife compared to journals where 619 previous studies found gender equity.…”
contrasting
confidence: 84%
“…Our finding that the gender of the last authors was associated with a significant difference in 614 the rate at which full submissions were accepted at eLife stands in contrast with a number of 615 previous studies of journal peer review that reported no significant difference in outcomes of 616 papers submitted by male and female authors [85][86][87], or differences in reviewer's evaluations 617 based on the author's apparent gender [88]. This discrepancy may be explained in part by 618 eLife's unique context, policies, or the relative selectivity of eLife compared to journals where 619 previous studies found gender equity.…”
contrasting
confidence: 84%
“…However, peer review may also be subject to systemic biases that influence editorial outcomes (Lee, Sugimoto, Zhang, & Cronin, ). For example, reviewers rate papers with famous authors, or authors from prestigious institutions, more highly (Tomkins, Zhang, & Heavlin, ). Editors and reviewers may also exhibit biases, conscious, or unconscious, against authors who speak a different language or reside in a different country from themselves (Lee et al, ; Murray et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…(Tamblyn, Girard, Qian, & Hanley, 2018), that we are subject to conscious and unconscious biases (Fay, 1993;Steinpreis, Anders, & Ritzke, 1999). The evidence on bias in peer review is mixed, with some studies concluding that bias occurs (Link, 1998;Tomkins, Zhang, & Heavlin, 2017;Tushingham, Fulkerson, & Hill, 2017), and other studies finding no significant impact (Lee, 2012), for example, Burns and Fox (2017) concluded that socioeconomics and language are more important factors than editor or reviewer bias in explaining geographic variation in acceptance rates ; and see also Engqvist & Frommen, 2008). Authorsuggested reviewers have been found to be more favourable than editor-selected reviewers (Bornmann & Daniel, 2010;Fox, Burns, Muncy, Meyer, & Thompson, 2017).…”
Section: F4 -Confidentialitymentioning
confidence: 99%